PENGARUH IKATAN KEPENTINGAN KEUANGAN, PEMBERIAN JASA LAIN, AUDIT TENURE, PERSAINGAN KANTOR AKUNTAN PUBLIK DAN AUDIT FEE TERHADAP INDEPENDENSI PENAMPILAN AUDITOR - Tiara Milka Wicita; Maria Stefani Osesoga (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
The purpose of this study was to examine the impact of the financial interest, non-audit services, audit tenure, competition between Public Accountant Firm, and audit fee toward auditor’s independency in appearance. The study was conducted using a survey method to provide the questionnaries to auditors in Public Accountant Firm. The data used in this study was primary data. The population of this study was auditors working at Public Accountant Firm. The sample of this study were auditors working at Public Accountant Firm in Jakarta and Tangerang which provides non-accounting services at least in one year of service and bachelor degree in level of education. There were 185 questionnaries distributed for this research, but only 134 questionnaries returned and 126 questionnaries used in this research using multiple linear regressions. The result of this study were (1) financial interest has no impact toward auditor’s independency in appearance, (2) non-audit services has no impact toward auditor’s independency in appearance,(3) audit tenure has no impact toward auditor’s independency in appearance, (4) competition between Public Accountant Firm has no impact toward auditor’s independency in appearance, (5) audit fee has significant impact toward auditor’s independency in appearance.